2016
DOI: 10.1016/j.bbadis.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of the astrocytic glutamate transporter GLT-1 is altered in mouse models of Lafora disease

Abstract: Lafora disease (LD, OMIM 254780) is a fatal rare disorder characterized by epilepsy and neurodegeneration. Although in recent years a lot of information has been gained on the molecular basis of the neurodegeneration that accompanies LD, the molecular basis of epilepsy is poorly understood. Here, we present evidence indicating that the homeostasis of glutamate transporter GLT-1 (EAAT2) is compromised in mouse models of LD. Our results indicate that primary astrocytes from LD mice have reduced capacity of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
(64 reference statements)
1
24
0
1
Order By: Relevance
“…One recent study suggested that there is preferential loss of GABAergic inhibitory interneurons 15 . Another reported that astrocytic glutamate clearance is impaired 16 , and there are yet other working hypotheses. In any case, perampanel would likely confer benefit by diminishing neuronal network hyper-excitability at least in part through its known AMPA antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggested that there is preferential loss of GABAergic inhibitory interneurons 15 . Another reported that astrocytic glutamate clearance is impaired 16 , and there are yet other working hypotheses. In any case, perampanel would likely confer benefit by diminishing neuronal network hyper-excitability at least in part through its known AMPA antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies on the mouse model of this disease have indicated a disruption in the homeostasis of the glutamate transporter GLT‐1 (EAAT2), resulting in reduced capacity of glutamate transport. This is consistent with the anti‐seizure mechanisms of action of VNS which include, as mentioned above, anti‐glutamatergic effects (Muñoz‐Ballester et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, se ha visto que la homeostasis del transportador del glutamato GLT-1, denominado EAAT2 en humanos y responsable de la recaptación del 90% del glutamato en el sistema nervioso central, se ve comprometida en ratones Epm2a -/y Epm2b -/-, observándose niveles disminuidos en la membrana plasmática de los astrocitos. Esto podría asociarse a la hiperexcitabilidad y la muerte neuronal que se produce en la LD [56]. Asimismo, se ha visto un incremento del número de astrocitos reactivos y microglía en ratones modelo de la enfermedad de ambos genes, así como un incremento de la expresión de genes que codifican citoquinas y mediadores de la respuesta inflamatoria [57].…”
Section: Nuevas Perspectivas Más Allá Del Metabolismo Del Glucógenounclassified